A novel role for central ACBP/DBI as a regulator of long‐chain fatty acid metabolism in astrocytes. (6th February 2015) - Bouyakdan, Khalil; Taïb, Bouchra; Budry, Lionel; Zhao, Shangang; Rodaros, Demetra; Neess, Ditte; Mandrup, Susanne; Faergeman, Nils. J.; Alquier, Thierry
Abstract Acyl‐CoA‐binding protein (ACBP) is a ubiquitously expressed protein that binds intracellular acyl‐CoA esters. Several studies have suggested that ACBP acts as an acyl‐CoA pool former and regulates long‐chain fatty acids (LCFA) metabolism in peripheral tissues. In the brain, ACBP is known as Diazepam‐Binding Inhibitor, a secreted peptide acting as an allosteric modulator of the GABAA receptor. However, its role in central LCFA metabolism remains unknown. In the present study, we investigated ACBP cellular expression, ACBP regulation of LCFA intracellular metabolism, FA profile, and FA metabolism‐related gene expression using ACBP‐deficient and control mice. ACBP was mainly found in astrocytes with high expression levels in the mediobasal hypothalamus. We demonstrate that ACBP deficiency alters the central LCFA‐CoA profile and impairs unsaturated (oleate, linolenate) but not saturated (palmitate, stearate) LCFA metabolic fluxes in hypothalamic slices and astrocyte cultures. In addition, lack of ACBP differently affects the expression of genes involved in FA metabolism in cortical versus hypothalamic astrocytes. Finally, ACBP deficiency increases FA content and impairs their release in response to palmitate in hypothalamic astrocytes. Collectively, these findings reveal for the first time that central ACBP acts as a regulator of LCFA intracellular metabolism in astrocytes. <boxed-text content-type="graphic" id="jnc13035-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Acyl‐CoA‐binding protein (ACBP) or diazepam‐binding inhibitor is a secreted peptide acting centrally as a GABAA allosteric modulator. Using brain slices, cortical, and hypothalamic astrocyte cultures from ACBP KO mice, we demonstrate that ACBP mainly localizes in astrocytes and regulates unsaturated but not saturated long‐chain fatty acids (LCFA) metabolism. In addition, ACBP deficiency alters FA metabolism‐related genes and results in intracellular FA accumulation while affecting their release. Our results support a novel role for ACBP in brain lipid metabolism. FA, fatty acids; KO, knockout; PL, phospholipids; TAG, triacylglycerol.